Gender-Dependent Alteration of Ca2+ and TNFα Signaling in db/db Mice, an Obesity-Linked Type 2 Diabetic Model - Delgado, Carmen; Gomez, Ana-Maria; Samia El Hayek, Magali; Ruiz-Hurtado, Gema; Pereira, Laetitia (Frontiers in Physiology, 2019)
Cardiovascular complications are the primary death cause in type 2 diabetes, where inflammation can play a role. We and others have previously shown that cardiac dysfunction is associated with cardiomyocyte Ca2+ mishandling in diabetic cardiomyopathy. It is possible that diabetic cardiomyopathy differently affects men and women, as the latter present higher risk to develop heart failure and a higher plasmatic level of the proinflammatory cytokine, Tumor Necrosis Factor alpha (TNFα) than men. However, the gender-dependent regulation of Ca2+ signalling in diabetes and its relationship with TNFα signalling is still unclear. Here, we analyzed TNFα signalling pathway and its role in Ca2+ signalling dysfunction in male and female rodent model of type 2 diabetes (db/db mice) using confocal microscopy in freshly isolated cardiomyocytes. TNFα increased [Ca2+]i transient amplitude and accelerated its decay without affecting SR Ca2+ load or Ca2+ spark frequency in cells from control mice. All TNFα effects on Ca2+ handling were prevented by the inhibition of the ceramidase and the PLA2. While the plasmatic level of TNFα was similar in male and female db/db mice, only male db/db hearts over-expressed both TNFα converting enzyme (TACE) and the protective TNFα receptors 2 (TNF-R2). TNFα receptor 1 (TNF-R1) expression, involved in negative inotropic response of TNFα, was unchanged in both male and female db/db mice compared to controls. We found that male db/db mice cardiomyocytes presented a decrease in [Ca2+]i transient amplitude associated to a drop of sarcoplasmic reticulum Ca2+ load, not seen in female db/db mice. Interestingly, sustained incubation with TNFα did not restored Ca2+ signalling alteration observed in male db/db mice but still induces an increase in Ca2+ sparks frequency as seen in control littermates. In cardiomyocytes from female db/db mice, TNFα had no visible effects on Ca2+ handling. In conclusion, our study shows that the alteration of Ca2+ signalling and TNFα, seen in db/db mice, are gender specific presenting an increase of TNFα cardio-protective pathway in male mice.